Toxoplasmose gestacional: acompanhamento do pré-natal, parto e desfechos de pacientes atendidas no Hospital Universitário de Santa Maria - Signori, Gabriela Kandler (2022)
Gestational Toxoplasmosis is an infectious disease caused by the protozoan Toxoplasma gondii, often asymptomatic, however there can be serious consequences due to the possibility of fetal damage. In 2018, the city of Santa Maria - RS suffered an outbreak of toxoplasmosis, considered in relative numbers, the largest outbreak of toxoplasmosis in the world, affecting the general population of the municipality, among them pregnant women. As a result of this study, the objective of this study is to evaluate prenatal care and delivery of pregnant women with a diagnosis of gestational toxoplasmosis and to define neonatal outcomes in patients treated at the obstetrics service of the University Hospital of Santa Maria (HUSM) – RS. This is a cross-sectional quantitative study, with a retrospective approach, from January 2017 to October 2019. A descriptive analysis was performed and the variables when quantitative were expressed using mean and standard deviation and the qualitative variables were expressed by absolute frequency (n) and relative frequency (%). The study comparing the ethical precepts contained in CNS Resolution No.466/2012 and was approved by the Ethics Committee of UFSM (opinion no. 2,814,895 and CAAE 1 59366116.5.0000.5346). The study population consisted of 108 pregnant women with serological diagnosis of gestational toxoplasmosis. Regarding the origin of these patients, all of them lived in an urban perimeter and the vast majority came from the periphery, of which it was observed that 52 (54.2%) came from the west part of the city. No cases were recorded in the rural area. Most infections were primary (94.4%) and there were 6 (5.5%) cases of reinfection. On symptomatology, most of the infected had symptomatology (54.7%) and the most frequent symptom was lymphadenomegaly. Forty-four amniocentesis were performed, of which 2 (4.5%) patients obtained PCR results from positive amniotic fluid, determining fetal infection. Among the positive ones, all had unfavorable gestational outcome, with fetal death and neonatal death. Regarding fetal outcomes, 90 (83.3%) cases were live newborns, 6 (5.5%) had abortion and 2 (2.5%) cases of fetal death. On the diagnosis of congenital toxoplasmosis, the majority (53%) obtained a negative result for congenital toxoplasmosis, while 25.3% with a positive result. Most pregnant women received treatment during pregnancy. On placental PCR, 24 analyses were performed, among which 2 with positive results. The fetal outcome in one of them was unfavorable with fetal death and the other with favorable outcome of live newborn.